Laue‐DIC: a new method for improved stress field measurements at the micrometer scale. (8th May 2015) - Petit, J.; Castelnau, O.; Bornert, M.; Zhang, F. G.; Hofmann, F.; Korsunsky, A. M.; Faurie, D.; Le Bourlot, C.; Micha, J. S.; Robach, O.; Ulrich, O.
<x xml:space="preserve">Abstract</x> A better understanding of the effective mechanical behavior of polycrystalline materials requires an accurate knowledge of the behavior at a scale smaller than the grain size. The X‐ray Laue microdiffraction technique available at beamline BM32 at the European Synchrotron Radiation Facility is ideally suited for probing elastic strains (and associated stresses) in deformed polycrystalline materials with a spatial resolution smaller than a micrometer. However, the standard technique used to evaluate local stresses from the distortion of Laue patterns lacks accuracy for many micromechanical applications, mostly due to (i) the fitting of Laue spots by analytical functions, and (ii) the necessary comparison of the measured pattern with the theoretical one from an unstrained reference specimen. In the present paper, a new method for the analysis of Laue images is presented. A Digital Image Correlation (DIC) technique, which is essentially insensitive to the shape of Laue spots, is applied to measure the relative distortion of Laue patterns acquired at two different positions on the specimen. The new method is tested on an in situ deformed Si single‐crystal, for which the prescribed stress distribution has been calculated by finite‐element analysis. It is shown that the new Laue‐DIC method allows determination of local stresses with a strain resolution of the order of 10−5.